Financial Costs of Meeting Global Biodiversity Conservation Targets: Current Spending and Unmet Needs - McCarthy, Donal P.; Donald, Paul F.; Scharlemann, Jörn P. W.; Buchanan, Graeme M.; Balmford, Andrew; Green, Jonathan M. H.; Bennun, Leon A.; Burgess, Neil D.; Fishpool, Lincoln D. C.; Garnett, Stephen T.; Leonard, David L.; Maloney, Richard F.; et al. (Science (American Association for the Advancement of Science), 2012)
World governments have committed to halting human-induced extinctions and safeguarding important sites for biodiversity by 2020, but the financial costs of meeting these targets are largely unknown. We estimate the cost of reducing the extinction risk of all globally threatened bird species (by > 1 International Union for Conservation of Nature Red List category) to be U.S. $0.875 to $1.23 billion annually over the next decade, of which 12% is currently funded. Incorporating threatened nonavian species increases this total to U.S. $3.41 to $4.76 billion annually. We estimate that protecting and effectively managing all terrestrial sites of global avian conservation significance (11,731 Important Bird Areas) would cost U.S. $ 65.1 billion annually. Adding sites for other taxa increases this to U.S. $76.1 billion annually. Meeting these targets will require conservation funding to increase by at least an order of magnitude.